Kufast: A tool for multi-tenancy in autonomous driving testbeds - Benjamin Acar; Marc Guerreiro Augusto (SoftwareX, 2023)
For the development and testing of autonomous driving technologies, there is a need for a robust and reliable testbed infrastructure that can support the deployment and testing of multiple applications from different tenants’s in parallel. We propose a multi-tenancy approach for autonomous driving testbeds to address this issue. In our approach, multiple users are able to deploy and test their applications on a shared infrastructure without interfering with each other. We have developed a tool called Kufast for the automation of the deployment process and the isolation of each tenants resources. This tool allows users to deploy their applications quickly and easily without advanced technical skills, and provides a user-friendly Command Line Interface.